2020
DOI: 10.1142/s179343112050013x
|View full text |Cite
|
Sign up to set email alerts
|

Design, Optimization and Nonlinear Response Control Analysis of the Mega Sub-Controlled Structural System (MSCSS) Under Earthquake Action

Abstract: The lately proposed mega sub-controlled structure (MSCSS) remarkably improved the seismic resistance ability and reduced vibration effects much more than the mega substructure (MSS). However, the controlling effectiveness and its optimization remain a significant concern. In this paper, a new configuration of MSCSS is analyzed in which viscous dampers are optimally arranged between mega-frame and substructural frame and optimal damper parameters are investigated. Also, rubber bearings are designed and introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The analytical model of the newly proposed MSCSS is represented as a simplified three-lumped-mass model based on the two-lumped-mass model presented for base isolation structures by Kelly, who employed an equivalent linear model to represent the hysteretic behavior of the isolation system. [27,28] The elevation view along with plans of different sections in the traditional MSS, improved MSCSS [9] and newly proposed MSCSS configurations are shown in Figure 1.…”
Section: Dynamic Equation Of Motion Of the Proposed Mscss Under Seism...mentioning
confidence: 99%
See 3 more Smart Citations
“…The analytical model of the newly proposed MSCSS is represented as a simplified three-lumped-mass model based on the two-lumped-mass model presented for base isolation structures by Kelly, who employed an equivalent linear model to represent the hysteretic behavior of the isolation system. [27,28] The elevation view along with plans of different sections in the traditional MSS, improved MSCSS [9] and newly proposed MSCSS configurations are shown in Figure 1.…”
Section: Dynamic Equation Of Motion Of the Proposed Mscss Under Seism...mentioning
confidence: 99%
“…F I G U R E 1 Configurations: (a) MSS, (b) MSCSS by Abdulhadi et al, [9,10] The dynamic equation of motion for the superstructure (i.e., above the mid-story isolator) for the proposed MSCSS under seismic excitation can be expressed as…”
Section: Dynamic Equation Of Motion Of the Proposed Mscss Under Seism...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the study, additional columns, as shown in Figure 1, are added above each MSCSS sub-frame to reduce the excessive bending moments in mega-beams so that the larger spans of the mega-beams can be achieved. Fan et al (2020) and Abdulhadi et al (2020) have demonstrated that if lead rubber bearings (LRBs) are installed between the additional columns and the mega-beams as shown in Figure 1, that is to release the connections between sub-frames and the upper mega-beams, the seismic performance of MSCSS can be further improved. In the past, most studies on MSCSS used the story drift ratio (SDR), acceleration, or energy dissipation as indicators to measure the effect of vibration control (Zhang et al 2005(Zhang et al , 2009Limazie et al 2013;Fan et al 2020).…”
Section: Introductionmentioning
confidence: 99%